A new species of Pelagobia (Lopadorrhynchidae, Annelida), with some notes on literature records of Pelagobia longicirrata Greeff, 1879 - Kolbasova, G.; Neretina, T. (Zootaxa, 2021)
Since the second half of the XX century, almost all Pelagobia samples from the Arctic, Antarctic, Atlantic and Pacific oceans had been identified as cosmopolitan P. longicirrata. The indistinct nuchal organs in P. longicirrata samples from the South China Sea (Spratly Islands and Taiwan) were considered a morphological feature of the Pacific population. Our morphological and genetic investigation of Pelagobia specimens from the Nhatrang Bay, Vietnam reveals a new species in this region. Pelagobia rubromaculata sp. nov. differs from P. longicirrata by its triangle head, with nuchal organs closely adjacent to the lateral sides of prostomium, by short tentacular cirri reaching only the posterior edge of the third segment, and by a specific colouration pattern with red spots. Using nuclear 18S and 28S rDNA markers reveals that P. rubromaculata sp. nov. forms a well-supported clade, confirming the validity of the new species. Phylogenetic analysis of all available P. longicirrata sequences using both single 18S and concatenated 18S and 28S genes shows at least three distinct clades: Central Atlantic, Arctic and South Atlantic. Antarctic specimens do not form any distinct clade and fall between other clades with low support.